Capital regulation: Less really can be more when incentives are socially aligned. Comments on Richard J. Herring "The Evolving Complexity of Capital Regulation". "The Interplay of Financial Regulations, Resilience, and Growth", Federal Reserve Bank of Philadelphia June 16-17, 2016 - Joseph P. Hughes (Rutgers University, Department of Economics, 2017)
Capital regulation has become increasingly complex as the largest financial institutions arbitrage differences in requirements across financial products to increase expected return for any given amount of regulatory capital, as financial regulators amend regulations to reduce arbitrage opportunities, and as financial institutions innovate to escape revised regulations - a regulatory dialectic. This increasing complexity makes monitoring bank risk-taking by markets and regulators more difficult and does not necessarily improve the risk sensitivity of measures of capital adequacy. Explaining the arbitrage incentive of some banks, several studies have found evidence of dichotomous capital strategies for maximizing value: a relatively low-risk strategy that minimizes the potential for financial distress to protect valuable investment opportunities and a relatively high-risk strategy that, in the absence distress costs due to valuable investment opportunities, "reaches for yield" to exploit the option value of implicit and explicit deposit insurance. In the latter case, market discipline rewards risk-taking and, in doing so, tends to undermine financial stability. The largest financial institutions, belonging to the latter category, maximize value by arbitraging capital regulations to "reach for yield." This incentive can be curtailed by imposing "pre-financial-distress" costs that make less risky capital strategies optimal for large institutions. Such potential costs can be created by requiring institutions to issue contingent convertible debt (COCOs) that converts to equity to recapitalize the institution well before insolvency. The conversion rate significantly dilutes existing shareholders and makes issuing new equity a better than than conversion. The trigger for conversion is a particular market-value capital ratio. Thus, the threat of conversion tends to reverse risk-taking incentives - in particular, the incentive to increase financial leverage and to arbitrage differences in capital requirement across investments.
Keywords: G21; G28; 330; banking; capital regulation; contingent convertible debt